On one atypical scheme of application of the second Lyapunov method - Sosnitskii, S. P. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
The second Lyapunov method is applied to the analysis of stability of triangular libration points in a three-dimensional restricted circular three-body problem. It is shown that the triangular libration points are unstable.